Approximate Gröbner Bases, Overdetermined Polynomial Systems, and Approximate GCDs. (21st March 2013) - Lichtblau, Daniel
Abstract : We discuss computation of Gröbner bases using approximate arithmetic for coefficients. We show how certain considerations of tolerance, corresponding roughly to absolute and relative error from numeric computation, allow us to obtain good approximate solutions to problems that are overdetermined. We provide examples of solving overdetermined systems of polynomial equations. As a secondary feature we show handling of approximate polynomial GCD computations, using benchmarks from the literature.